Ontological evaluation in the knowledge based system - Bueno, Tânia C. D. (2006)
In the last few years, several studies have emphasized the use of ontologies as an alternative to organization of the information. The notion of ontology has become popular in fields such as intelligent information integration, information retrieval on the Internet, and knowledge management. Different groups use different approaches to develop and verify de effectiveness of ontologies. This diversity can be a factor that makes the formularization difficult of formal methodologies of evaluation. This paper intends to provide a way to identify the effectiveness of knowledge representation based on ontology that was developed through Knowledge Based System tools. The reason is that all processing and storage of gathered information and knowledge base organization is performed using this structure. Our evaluation is based on case studies of the KMAI system, involving real world ontology for the money laundry domain. Our results indicate that modification of ontology structure can effectively reveal faults, as long as they adversely affect the program state.